Atomically Dispersed Single Ni Site Catalysts for Nitrogen Reduction toward Electrochemical Ammonia Synthesis Using N2 and H2O. Issue 6 (5th February 2020) - Mukherjee, Shreya; Yang, Xiaoxuan; Shan, Weitao; Samarakoon, Widitha; Karakalos, Stavros; Cullen, David A.; More, Karren; Wang, Maoyu; Feng, Zhenxing; Wang, Guofeng; Wu, Gang
Abstract: Ammonia (NH3 ) electrosynthesis gains significant attention as NH3 is essentially important for fertilizer production and fuel utilization. However, electrochemical nitrogen reduction reaction (NRR) remains a great challenge because of low activity and poor selectivity. Herein, a new class of atomically dispersed Ni site electrocatalyst is reported, which exhibits the optimal NH3 yield of 115 µg cm −2 h −1 at –0.8 V versus reversible hydrogen electrode (RHE) under neutral conditions. High faradic efficiency of 21 ± 1.9% is achieved at ‐0.2 V versus RHE under alkaline conditions, although the ammonia yield is lower. The Ni sites are stabilized with nitrogen, which is verified by advanced X‐ray absorption spectroscopy and electron microscopy. Density functional theory calculations provide insightful understanding on the possible structure of active sites, relevant reaction pathways, and confirm that the Ni‐N3 sites are responsible for the experimentally observed activity and selectivity. Extensive controls strongly suggest that the atomically dispersed NiN3 site‐rich catalyst provides more intrinsically active sites than those in N‐doped carbon, instead of possible environmental contamination. This work further indicates that single‐metal site catalysts with optimal nitrogen coordination is very promising for NRR and indeed improves the scaling relationship of transition metals. Abstract : An atomically dispersed Ni site with three N coordination (NiN3 ) is prepared and exhibits encouraging nitrogen reduction reaction (NRR) activity and faradic efficiency in a variety of electrolytes. The synthesis–structure–property correlations are determined by combining controlled synthetic chemistry, high‐resolution characterization, and density functional theory calculations.